PENERAPAN METODE PEMBELAJARAN INKUIRI SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR DAN PRESTASI BELAJAR KOMPETENSI ALAT UKUR SISWA KELAS X TEKNIK KENDARAAN RINGAN SMK AL-MUJAHIDIN NW KUMBUNG LOMBOK TIMUR TAHUN PELAJARAN 2016/2017 - M. Amir Hadi; Slamet Priyanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study is to knowing: (1) can the application of inquiry learning methods increases learning motivation of measuring tool; and (2) can the application of inquiry learning methods increases learning achievement of measuring tool of Light Vehicle Engineering of Al-Mujahidin NW Kumbung East Lombok.This study included a Classroom Action Research. Subject of This research is Light Vehicle Engineering in 10th class of SMK Al-Mujahidin NW Kumbung which amounts to 18 students. While the object of this research is motivation of learning and achievement of measuring tool subjects. Data collection technique in this study uses the technique of questionnaires and tests. The Istrumen in this study uses the syllabus, lesson plans, questionnaires, tests and observation sheet. And than the data analysis technique uses descriptive and quantitative analysis to determine the percentage of student achievement.The results of this research showed that: (1) the application of inquiry learning methods on measuring tool subject can increases learning motivation, indicated with an average of Students learning motivation in 1st cycle 61.22, on the 2nd cycle 76.33, and on the 3rd cycle 90.17; And (2) the application of inquiry learning methods can increases student learning achievement on measuring tool subjects. this research showed that an increase in the average value of 49.44 in 1st cycle into 78.88 in the 2nd cycle and into 85.55 on the 3rd cycle before the action.